2016
DOI: 10.1007/s40808-016-0251-2
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the groundwater–saline water interaction in a complex coastal aquifer in South India using statistical and hydrochemical mixing models

Abstract: Hydrogeochemical investigations were carried out in a coastal aquifer along the East coast of Cuddalore district in Tamil Nadu, Southern India, to analyse the groundwater-seawater interactions. Multiple techniques including Hydrochemical Facies Evaluation Diagram (HFE-D), principle component analysis (PCA), ionic ratios, hydrochemical ionic changes models and salinity mixing index (SMI) models were applied to refine the results and exactly understand the salinization process. EC and Ionic constituents along wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 40 publications
(48 reference statements)
1
7
0
Order By: Relevance
“…The dominance of rock-water interaction suggests that groundwater in the area had sufficient time to interact with the lithology material and in the course of this interaction, different ions were released into the water. Similar results were obtained in a study done by [21,26,31] using the Gibbs plot to differentiate between mechanisms controlling groundwater and surface water chemistry. The majority of samples suggested that the chemical weathering of rock-forming minerals is influencing the groundwater quality.…”
Section: Hydrogeochemical Facies and Geochemical Processessupporting
confidence: 85%
See 1 more Smart Citation
“…The dominance of rock-water interaction suggests that groundwater in the area had sufficient time to interact with the lithology material and in the course of this interaction, different ions were released into the water. Similar results were obtained in a study done by [21,26,31] using the Gibbs plot to differentiate between mechanisms controlling groundwater and surface water chemistry. The majority of samples suggested that the chemical weathering of rock-forming minerals is influencing the groundwater quality.…”
Section: Hydrogeochemical Facies and Geochemical Processessupporting
confidence: 85%
“…Using the Gibbs plot, conclusions concerning the influence of various dominant geochemical processes such as precipitation, rock-water interaction mechanism and evaporation in controlling the hydrochemistry of groundwater in the aquifer can be deduced [21]. Most samples in the study region were confined in the rock-dominant and evaporation dominant zone (Fig.…”
Section: Hydrogeochemical Facies and Geochemical Processesmentioning
confidence: 99%
“…The Gibbs diagram can be used to display the evolution of groundwater composition and can indicate the mechanism that governs the chemical composition of groundwater, its evaporation, rock-water interaction or precipitation (Kumar 2016). Gibbs plots for this study using (TDS vs. Na/(Na + Ca), and Cl/(Cl + HCO3) suggest that evaporation is the main process controlling chemistry of the shallow groundwater (Fig.…”
Section: Gibbs Diagrammentioning
confidence: 90%
“…If the dissolutions of calcite, dolomite and gypsum are the foremost reactions in a system then the bivariate plot of Ca 2+ + Mg 2+ versus SO 4 2− + HCO 3 − will be close to the 1:1 line (Kanagaraj et al 2018;Kumar 2016). If the points shift more to the left due to an excess of SO 4 2− + HCO 3-this indicates ion-exchange as a result of silicate weathering.…”
Section: Bivariate Plotsmentioning
confidence: 97%
See 1 more Smart Citation